2007
DOI: 10.1097/fpc.0b013e32810f2e58
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcriptase-PCR quantification of mRNA levels from cytochrome (CYP)1, CYP2 and CYP3 families in 22 different human tissues

Abstract: This description will broaden the understanding of the physiological functions of these CYPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
222
5
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(249 citation statements)
references
References 58 publications
(72 reference statements)
20
222
5
2
Order By: Relevance
“…Previous data suggested that CYP2E1 mRNA is one of the most abundant transcript among CYPs (56% of total CYP mRNA), whereas the protein is relatively poorly expressed (7% of total CYP proteins). 44,45 Although this could reflect a particular ability of CYP2E1 transcripts to undergo significant degradation in normal circumstances, 46 acute CCl 4 intoxication could accelerate this putative CYP2E1 mRNA degradative pathway. Interestingly, current investigations in our laboratory also showed acetaminophen-induced early CCl 4 induces early mitochondrial alterations L Knockaert et al reduction of CYP2E1 mRNA levels (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data suggested that CYP2E1 mRNA is one of the most abundant transcript among CYPs (56% of total CYP mRNA), whereas the protein is relatively poorly expressed (7% of total CYP proteins). 44,45 Although this could reflect a particular ability of CYP2E1 transcripts to undergo significant degradation in normal circumstances, 46 acute CCl 4 intoxication could accelerate this putative CYP2E1 mRNA degradative pathway. Interestingly, current investigations in our laboratory also showed acetaminophen-induced early CCl 4 induces early mitochondrial alterations L Knockaert et al reduction of CYP2E1 mRNA levels (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The only known pathological condition associated with CYP2R1 disruption is the rare mutations identified in patients with 25(OH)D 3 deficiency and vitamin D-dependent rickets (22)(23)(24)(25)(26). CYP2R1 is primarily expressed in liver and testis (19,29,(32)(33)(34). The former is consistent with liver being the major site of 25-hydroxylation, but its abundance in testis awaits further investigation to decipher the physiological relevance, although it has been linked to male reproduction, testicular cancer, and other testiculopathic conditions (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The CYP1D subfamily, a non-mammalian subfamily which has been recently identified, contains a single CYP1D1 gene (Goldstone et al 2009). The liver is the major site of E 2 metabolism; all CYP1s and CYP3As are known to be expressed in the liver of mammals (Bieche et al 2007) and fish (Jonsson et al 2007, Goldstone et al 2009). …”
Section: Introductionmentioning
confidence: 99%